Integrating Rogoff's Sociocultural Development Theories for Effective Faith Transmission in Confessional Anglican Churches: A Case Study of Sydney Diocese - Beilharz, Tim (Christian education journal, 2023)
This article suggests an integration of Barbara Rogoff's sociocultural development theories into Christian faith transmission. Drawing from Confessional Anglican Churches in Sydney, it examines prevailing models of children's ministry influenced by Western schooling principles. Highlighting Rogoff's intent community participation and cultural learning theories, it argues for their applicability in fostering meaningful children's ministry practices among children and the alignment with Confessional Anglican theology. It concludes with suggestions for application in children's ministry practice.